Callus Induction of Fenugreek Trigonella Foenum-Graecum via Auxin Combined with Cytokinins Hormones, and Assessment of Toxicity via Brine Shrimp Assay - Agha, Hasan M; Radzun, Khairul Adzfa; Sidik, Norrizah Jafaar; Jawad, Ali H (Journal of Asian Scientific Research, 2022)
Trigonella foenum-graecum (TFG) is a significant leguminous plant with diverse pharmacological effects. However, the resistant character of this plant accounts for significant difficulties in vitro multiplication, justifying the necessity to try new techniques for in vitro propagation of this plant. Hence, this study reports the effects of BAP, NAA, and 2,4-D on in vitro callus formation of seeds. The toxicity properties of seeds, plant, and callus aqueous extracts of TFG were measured by brine shrimp assay (BSA). Callus index, frequency of callus, callus weight, and morphology of callus were recorded after 30 days of culture. No callus formation was observed in the absence of plant growth regulators. The maximum callus formation observed in the MS media containing 1.0 mg/l 2,4-D, the highest mean of the callus index (52±9.5) with 100% frequency and callus yield (0.52±0.08 g) in 30 days of culture. The highest mean of callus index (37±0 4.05) for combination hormones with 100% callusing and yield (0.37±0.02 g) in 30 days of culture by 1.0 mg/l BAA with 0.5 mg/l NAA. Seeds extract of TFG showed the highest toxicity (954.99 µg/ml), aqueous plant extract (1237.98 µg/ml), and aqueous callus extract (1801 µg/ml) from BSA. Comparing individual hormones, the highest amount of callus in TFG can be yielded 2,4-D hormone alone, and a combination of BAP and NAA can yield 100% callus.